Monte Carlo simulation of air kerma rate constants for different radionuclides - Paixão, Lucas; Cristina Ferreira Fonseca, Telma (Revista Brasileira de Física Médica, 2024)
The air kerma rate constant values for different radionuclides are often used in radiation shielding calculations, calibration of instruments, estimating the absorbed dose from brachytherapy sources, etc. Usually, air kerma rate constant values are calculated in a deterministic way. This work evaluates the possibility of air kerma rate constant estimation through Monte Carlo simulations. Ten different radionuclides were considered in this preliminary study, covering low and high-energy gamma spectra. Mean percentage differences of less than 10% relative to the results of reference works were found. Most of our results (C-11, O-15, F-18, Ga-67, Ga-68, I-131, and Tl-201 sources) present less than a 5% relative percentage difference considering the literature results. The air kerma rate constants calculated in this work agree with reference results, thus validating the methodology, the photon spectra database used, and the Monte Carlo simulations with EGSnrc. Future work can extend the calculation of air kerma rate constants for other radionuclides and study the influence of different sources of uncertainty in its results.